DISTANCE EDUCATION AS A PROMISING SECTOR OF THE ECONOMY - Anpilohova, Tetiana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article describes the features distance higher education in the world is characterized by as well as advantages and disadvantages of it. Author provides brief outline of the role of distance education in developed and developing countries. One can find the explanation why distance education under current war situation in Ukraine has aggravated a number of psychological problems.